Inverse shoulder tumor megaprosthesis after large bone resection in massive metastasis of the proximal humerus - Cardinale, Umberto; Pisanu, Francesco; Marco, Pes; Ciatti, Corrado; Manunta, Andrea Fabio; Doria, Carlo (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Bone metastases are a significant prognostic factor in the history of cancer and often involve pain and a great impairment of the quality of life. The complete resection of tumor tissue is increasingly performed in patients with solitary bone metastases, to improve the survival of patients and their functional outcomesMethods: We report the case of a 65-year-old man with a painful, massive, highly perfused osteolytic lesion localized at the proximal third of the humerus, associated with extensive lesions of the rotator cuff tendons was diagnosed with keratoblastic squamous cell lung cancer metastasis.Results: The patient underwent shoulder and proximal humerus reconstruction with inverse tumor megaprosthesis after embolization of the lesion. At 3 and 6 months FU, a nearly complete resolution of painful symptoms, a significant improvement in functional skills, and better execution of most of the activities of daily life have been reported.Conclusions: Accordingly with the literature the inverse shoulder megaprosthesis seems able to restore a satisfactory function and the silver-coated modular tumor system appears as a safe and viable treatment option in metastases tumor of proximal humerus.